Hexamethylene diisocyanate, 2, 4‐toluene diisocyanate, 2, 6‐toluene diisocyanate, isophorone diisocyanate and 4, 4′‐methylene diphenyl diisocyanate – Determination of hexamethylenediamine, 2, 4‐toluenediamine, 2, 6‐toluenediamine, isophoronediamine and 4, 4′‐methylenedianiline in urine using gas chromatography‐mass spectrometry [Biomonitoring Methods, 2017]. Issue 3 (31st July 2017) - Cocker, J.; Jones, K.; Leng, G.; Gries, W.; Budnik, L.T.; Müller, J.; Göen, T.; Hartwig, A.; ,
Abstract: The working group "Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the present biomonitoring method. The described method allows the simultaneous determination of the metabolites of hexamethylene diisocyanate (HDI ), 2, 4‐toluene diisocyanate and 2, 6‐toluene diisocyanate (TDI ), isophorone diisocyanate (IPDI ) and methylene diphenyl diisocyanate (MDI) in human urine. After acid hydrolysis the released amines, hexamethylenediamine (HDA ), 2, 4‐toluenediamine, and 2, 6‐toluenediamine (TDA ), isophorone diamine (IPDA ) and 4, 4′‐methylenedianiline (4, 4 ′‐MDA ) are extracted from urine, derivatised using heptafluorobutyric anhydride and quantified by NCI‐GC‐MS. The method was extensively validated and the reliability data were confirmed by independent laboratories, which have established and cross‐checked the whole procedure.